Discovery and characterization of stable and toxic Tau/phospholipid oligomeric complexes. Issue 1 (December 2017) - Ait-Bouziad, Nadine; Lv, Guohua; Mahul-Mellier, Anne-Laure; Xiao, Shifeng; Zorludemir, Gizem; Eliezer, David; Walz, Thomas; Lashuel, Hilal
Abstract The microtubule-associated protein Tau plays a central role in the pathogenesis of Alzheimer's disease. Although Tau interaction with membranes is thought to affect some of its physiological functions and its aggregation properties, the sequence determinants and the structural and functional consequences of such interactions remain poorly understood. Here, we report that the interaction of Tau with vesicles results in the formation of highly stable protein/phospholipid complexes. These complexes are toxic to primary hippocampal cultures and are detected by MC-1, an antibody recognizing pathological Tau conformations. The core of these complexes is comprised of the PHF6* and PHF6 hexapeptide motifs, the latter in a β-strand conformation. Studies using Tau-derived peptides enabled the design of mutants that disrupt Tau interactions with phospholipids without interfering with its ability to form fibrils, thus providing powerful tools for uncoupling these processes and investigating the role of membrane interactions in regulating Tau function, aggregation and toxicity. The Alzheimer protein Tau interacts with biological membranes, but the role of these interactions in regulating Tau function in health and disease remains unexplored. Here, the authors report on the discovery and characterization of neurotoxic oligomeric protein/phospholipid complexes.